Local and Global Geographies of Innovation: Structures, Processes, and Geographical Contexts from a Firm Perspective. (16th May 2014) - Rusten, Grete; Overå, Ragnhild
Abstract This paper introduces a special issue addressing the relationship between innovations and geographical contexts. The content, role, and sourcing of knowledge and how this relates to production systems and particular innovation projects is addressed. It includes a discussion about how firm strategies and organizational arrangements such as sourcing strategies, brokering arrangements, and project bundling effects the position of clusters as a knowledge source. Part of this discussion refers to the content of the three papers that follows.